ANALISIS POTENSI TAMAN WISATA ALAM SEMONGKAT DALAM MENINGKATKAN PENDAPATAN ASLI DESA (Studi di Desa Kelungkung Kecamatan Batu Lanteh) - Maharani, Feny Dwi; Wardanny, Sherli; Marselah, Rahmi (Jurnal Ekonomi & Bisnis, 2025)
This study aims to analyze the potential of Semongkat Nature Tourism Park (TWA) in increasing the Original Village Revenue (PADes) of Kelungkung Village, Batu Lanteh District, Sumbawa Regency. The research used a qualitative descriptive approach. Data collection was conducted using interviews, observation, and documentation. The subjects of this research consisted of the Head of Government and the Head of Service at the Kelungkung Village Office, Batu Lanteh Sub-District. Data analysis was conducted descriptively by adopting and adapting the SWOT analysis model, a qualitative analysis that examines internal and external factors. Internal factors, in this case, are strengths and weaknesses. External factors consist of opportunities and threats. SWOT analysis showed that TWA Semongkat's main strengths lie in its preserved natural beauty and improving tourism infrastructure. However, challenges include the village's limited authority over management, the weak role of the village-owned enterprise (BUMDes), and unequal economic impact across sub-villages. Opportunities exist in strengthening BUMDes, collaborating with the tourism-aware community group (Pokdarwis), and optimizing village-owned assets. Threats arise from the lack of formal cooperation with BKSDA and high dependence on informal economic activities. The study concludes that strategic collaboration and local capacity development are essential to maximizing TWA Semongkat’s contribution to Kelungkung Village's PADes.